(Ight ima need some help!! ) solve the following equation (2x + 3) (3x + 2) − (3x + 2) (2x− 3) = 0. solve for x and show work
(2x + 3) (3x + 2) − (3x + 2) (2x− 3) = 0

Respuesta :

Answer:

x = [tex]-\frac{2}{3}[/tex]

Step-by-step explanation:

I used the FOIL method

[(2x + 3) (3x + 2)] − [(3x + 2) (2x− 3)] = 0

[tex](6x^{2} +4x+9x+6) - (6x^{2} -9x+4x-6)=0[/tex]

[tex](6x^{2} +13x+6) - (6x^{2} -5x-6)=0[/tex]

[tex](6x^{2} +13x+6) - 6x^{2} +5x+6=0[/tex]

combine like terms

[tex]6x^{2} -6x^{2} = 0[/tex]

[tex]13x+5x=18x[/tex]

[tex]6+6=12[/tex]

so, [tex]18x +12 = 0[/tex]

subtract 12 on both sides

[tex]18x=-12[/tex]

divide by 18 to isolate x

[tex]x=-\frac{12}{18}[/tex]

and simplifies to

[tex]x=-\frac{2}{3}[/tex]